Home Environmental Factors and Science Anxiety Affecting Academic Performance of Pre-Service Science Teachers - Mendez, Mercy Joy; Nacional, Anjanette; Quilos, Danica Jade; Salva, Loren Hazel Mae (SEAMEO QITEP in Science, 2023)
This study aims to identify the significant relationship between the home environmental factors and science anxiety affecting the academic performance of all pre-service science education students at the University of Mindanao. The total data from this study came from 124 respondents who participated in completing the survey and was collected using a descriptive correlation design. The researchers used a random sampling technique to select the respondents. Using mean and Pearson r analysis revealed a significant relationship between home environmental factors and science anxiety affecting the academic performance of pre-service science teachers. The study found that parents' socioeconomic status and student attitude resulted in a high mean and reached a high level. In contrast, parental involvement reached a moderate level. Science Anxiety with an indicator of science content showed low anxiety levels. The result revealed no significant relationship between the variables affecting the academic performance of pre-service science teachers. This study advocates the learners' various effects of dealing with anxiety about the factors from the home environment and academic performance. It may consider giving guidance and support such as that will provide interest and motivation to students.